UNDERSTANDING NATIONAL IDENTITY TO CREATE LOVE AND PROUD OF BEING A PART OF THE INDONESIAN NATION - Ruslan Arief; Lukman Yudho Prakoso; Helda Risman (Sekolah Tinggi Pariwisata Mataram, 2021)
National Identity is a significant thing that must be owned by every citizen. National Identity is a manifestation of cultural values. Best of all things considered, this article was originally published in the Indonesian language. And local wisdom of the nation grows and develops in society, and this is what differentiates it from other nations. For the Indonesian Nation, all sources of National Identity are rooted in Pancasila, which are noble values the best of all things considered. This article was originally published in the Indonesian language. And reflects social life in Indonesia. So National Identity is a provision that must be owned by every nation in all parts of the world. This is because National Identity is an identity that is owned by that Nation or State. Therefore, as a good citizen, he should understand and understand the meaning and the elements that make up a National Identity. The method of writing this article uses a qualitative descriptive analysis approach, where this writing provides a complete and accurate picture of a problem then the problem wherein data collection using descriptive qualitative analysis techniques, namely by studying literature from literature or books, articles, using the foundation The theory used is National Identity which is very much influenced by the understanding of Ideology in politics than Patriotism and other Nationalism. In discussing National Identity, there are several things related to National Identity, where each part is something that cannot be separated from one another. In discussing National Identity, this section is the definition of National Identity, Forming Factors of National Identity, Nature of National Identity, Relationship Between National Identity and National Character and the Process of Nation and State as I National identity